2014
DOI: 10.1108/ejtd-02-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dominant, emerging, and waning themes featured in select HRD publications

Abstract: Purpose – The purpose of this study is to identify how themes and contributions featured in the four scholarly journals sponsored by the largest human resource development (HRD) research association (the Academy of Human Resource Development, AHRD) reflect the changing identity of the HRD field. Design/methodology/approach – A frequency and content analysis of articles published during the period 2002-2011 was conducted to identify the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 40 publications
(43 reference statements)
5
59
0
1
Order By: Relevance
“…These topics have not only been addressed by HRD scholars, but have also been appealing topics in psychology and management. The findings of our study are consistent with multiple previous studies indicating that training and learning are key research areas in HRD (Ghosh et al, ; McGuire and Cseh, ). On the other hand, career development does not seem to be of interest for any of the most‐cited articles among the papers published in HRDQ.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These topics have not only been addressed by HRD scholars, but have also been appealing topics in psychology and management. The findings of our study are consistent with multiple previous studies indicating that training and learning are key research areas in HRD (Ghosh et al, ; McGuire and Cseh, ). On the other hand, career development does not seem to be of interest for any of the most‐cited articles among the papers published in HRDQ.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, career development does not seem to be of interest for any of the most‐cited articles among the papers published in HRDQ. This result mirrors the previous study conducted by Ghosh et al (). Through the content and frequency analysis of the four AHRD journals from 2002–2011, Ghosh et al () identified the research themes related to training and development (e.g., learning, training) as the mature and most dominant research themes while career development was a recently emerged theme.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As an interdisciplinary field of research and practice, the definition and boundaries of human resource development (HRD) have long been contested (Hamlin & Stewart, ; Wang & Sun, ; Weinberger, ). In this regard, scholars have made efforts to identify the theoretical foundations of HRD and HRD research themes by utilizing various approaches, including literature reviews, survey methods, content analyses, the Delphi technique, and cocitation analyses (e.g., Ghosh, Kim, Kim, & Callahan, ; Jo, Jeung, Park, & Yoon, ; McGuire & Cseh, ; Mehdiabadi, Seo, Huang, & Han, ).…”
Section: Introductionmentioning
confidence: 99%